2005
DOI: 10.2993/0278-0771(2005)25[129:isbrot]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Snake Bite Remedies of the Luo of Western Kenya

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
1
30
1
1
Order By: Relevance
“…The beliefs appear to be clanrelated and include snakes "can protect" (among the Baganda) [18,75] or "are dangerous and connected to witchcraft" in most communities [8]. By comparison, the Luo of Kenya associate snakes with witchcraft [76].…”
Section: Traditional Concept Of Snakebites In Ugandamentioning
confidence: 99%
“…The beliefs appear to be clanrelated and include snakes "can protect" (among the Baganda) [18,75] or "are dangerous and connected to witchcraft" in most communities [8]. By comparison, the Luo of Kenya associate snakes with witchcraft [76].…”
Section: Traditional Concept Of Snakebites In Ugandamentioning
confidence: 99%
“…Traditional herbal remedies provide health services even in highly industrialized setups because they are important pillars of culture and human socialization (Owuor et al, 2005). In many cases, plants used as herbal remedies are not only important as drugs but also as food supplements with vitamins and minerals (Duke, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This study has shown that the rural people of Nneochi rely heavily on herbal medicine to handle ante-natal and post-natal disorders which are chiefly responsible for maternal and child mortality. Traditional herbal remedies provide health services even in highly industrialized setups because they are important pillars of culture and human socialization (Owuor et al, 2005).…”
Section: Discussionmentioning
confidence: 99%